Internet use and alcohol consumption in university students - Armendáriz García, Nora Angélica; Estrada González, Erik Jahir; López García , Karla Selene; López Cisneros, Manuel Antonio; Villarreal Mata, Julia Lizeth (Horizonte Sanitario, 2025)
Objetive: Determine the relationship between internet use and alcohol consumption among university students. Materials and Methods: Descriptive, correlational and cross-sectional study. The sample size was 238 young university students. The type of sampling was random by clusters. Results: it was reported that 73.1% of young people had problematic Internet use. Significant differences (χ2 = 4.911, p= .027) were found in those who presented problematic Internet use; were those with the highest proportion of instant prevalence of alcohol consumption (63.5%), compared to those with moderate internet (36.5%). Regarding problematic Internet use, it showed a positive and significant relationship with alcohol consumption (rs= .162, p<.05).Conclusions: Internet use and alcohol consumption are behaviors that are increasing in young people, and these can be intensified by new forms of communication and social dynamics, which can have an important effect on the behavior of young university students. Key word: Internet, Alcohol Drinking, Students